The Immigrant Exodus : Why America Is Losing the Global Race to Capture Entrepreneurial Talent. - Wadhwa, Vivek (Wharton Digital Press, 2012)
Many of the United States' most innovative entrepreneurs have been immigrants, from Andrew Carnegie, Alexander Graham Bell, and Charles Pfizer to Sergey Brin, Vinod Khosla, and Elon Musk. Nearly half of Fortune 500 companies and one-quarter of all new small businesses were founded by immigrants, generating trillions of dollars annually, employing millions of workers, and helping establish the United States as the most entrepreneurial, technologically advanced society on earth. Now, Vivek Wadhwa, an immigrant tech entrepreneur turned academic with appointments at Duke, Stanford, Emory, and Singu.